2008
DOI: 10.1507/endocrj.k07e-130
|View full text |Cite
|
Sign up to set email alerts
|

Serum DHEA-S Level Is Associated with the Presence of Atherosclerosis in Postmenopausal Women with Type 2 Diabetes Mellitus

Abstract: Abstract. We investigated the relationship between serum dehydroepiandrosterone-sulfate (DHEA-S) and insulin-like growth factor-I (IGF-I) to various parameters for atherosclerosis in type 2 diabetes. The levels of DHEA-S and IGF-I are known to decrease with aging and thereby might be associated with an increased risk of cardiovascular disease. One hundred forty-eight men and 106 postmenopausal women with type 2 diabetes were assessed in a cross-sectional study. Serum DHEA-S and IGF-I concentrations were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
1
21
1
Order By: Relevance
“…On the other hand, AMPK phosphorylation occurred upon treatment with PDGF, a potent mitogen (Figs 2 and 3), which suggests that AMPK activation may not be strictly associated with growth inhibition. Although these data do not agree with the concept that AMPK has anti-proliferative activity (Motoshima et al 2006), two recent reports have shown that AMPK promotes the proliferation of osteoblastic cells and fibroblasts (Hattori et al 2006, Kanazawa et al 2008. In agreement with these findings, inhibition of AMPK blocked SMC proliferation in response to both PDGF and adiponectin, which thus implies that AMPK likely has a role in SMC proliferation.…”
Section: Discussioncontrasting
confidence: 53%
“…On the other hand, AMPK phosphorylation occurred upon treatment with PDGF, a potent mitogen (Figs 2 and 3), which suggests that AMPK activation may not be strictly associated with growth inhibition. Although these data do not agree with the concept that AMPK has anti-proliferative activity (Motoshima et al 2006), two recent reports have shown that AMPK promotes the proliferation of osteoblastic cells and fibroblasts (Hattori et al 2006, Kanazawa et al 2008. In agreement with these findings, inhibition of AMPK blocked SMC proliferation in response to both PDGF and adiponectin, which thus implies that AMPK likely has a role in SMC proliferation.…”
Section: Discussioncontrasting
confidence: 53%
“…Osteocalcin was found to be inversely associated with fasting plasma glucose (FPG) [7,9,10] , HbA1c [7,12] , body mass index (BMI) [10,13] , fat mass [10] , measures of insulin resistance [8,14] , and measures of lipid metabolism [12,15] . In these same studies, osteocalcin was positively associated with adiponectin [11] and measures of insulin sensitivity [7,15] . Among these studies, the positive relationship between osteocalcin and markers of metabolic phenotype were revealed mostly in the elderly population or subjects with diabetes mellitus.…”
Section: Introductionmentioning
confidence: 78%
“…A number of studies have evaluated the complex interactions between the skeleton and glucose and energy homeostasis in humans [7][8][9][10][11][12][13][14][15] . Osteocalcin was found to be inversely associated with fasting plasma glucose (FPG) [7,9,10] , HbA1c [7,12] , body mass index (BMI) [10,13] , fat mass [10] , measures of insulin resistance [8,14] , and measures of lipid metabolism [12,15] .…”
Section: Introductionmentioning
confidence: 99%
“…AMPK is well known as a key sensor of changes in cellular energy homeostasis such as lipid synthesis (Rutter & Leclerc 2009). With regard to bone metabolism, it has been shown that AMPK stimulates bone formation and mineralization (Kanazawa et al 2008, Shah et al 2010. It has recently been shown that AMPK stimulates osteoblast differentiation via induction of RUNX2 expression (Jang et al 2011).…”
Section: Discussionmentioning
confidence: 99%